The Level of Psychological Compatibility Among the Civilian Retirees in the Governorates of Northern Jordan in the Light of some Variables - Momeni, Muhammad Ali Al-Abdullah; Al-Kazemi, Esraa Baqer Jaafar; Momani, Adel Mustafa Salem (Journal of Educational and Psychological Sciences, 2018)
The study aimed at identifying the level of psychological compatibility among the civilian retirees in northern Jordan in the light of some variables. The study used the descriptive descriptive method of the questionnaire. The tool was in the compatibility scale for the elderly of Alaheddin (2004) and the Jordanian environment, which was distributed to a sample of 361 retirees . The results showed that the general compatibility ratio reached 56.5% with an average mean of 1.96 and a medium level. There were statistically significant differences due to the income effect in favor of the income category less than 200 JD. There were no statistically significant differences due to the health condition. Statistics attributed to the impact of the current work in favor of a class does not work, and in the light of the results was a set of recommendations and proposals to enhance the psychological compatibility of retirees